PENGAJARAN AKHLAK BERBASIS NASKAH SASTRA WULANG - Susiyanto, Susiyanto (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2018)
Sastra Wulang is a Javanist literature masterpiece that consists of advices and various discussion related to ethics. Classical text is an essential heritage for Javanist society character development. As in this javanist poet masterpiece, It puts a good character as an underlined case.Sastra Wulang often  discusses the values that become javanest people believe, especially related to morality. Those values generally come from Islam, however, it is translated in order to be matched with the local context. With this method, thus the concepts taken from a religion would be more familiar and become a part of society understanding.Therefore,  discussing Sastra Wulang  text in order to be recognized by young generation becomes an urgent problem. The purpose is to make the young generation can appreciate correctly the old era heritage. They will not only learn about cultural aspects, but at the same time, this method can also strengthen their understanding about Islam. The involvement of students in accessing sastra wulang activities,  is expected that  an education process conducted would be more comprehensive to combine a number of disciplines, such as the science of cultur, history, art, religion and other disciplines.